A Review of Taxation Aspect of Cash Poolings Based on Indonesian Regulations - Yanurwenda, Benny Oktis; Suryawati, Rindah Febriana (Directorate General of Taxes, 2025)
Cash poolings are typically formed by companies in a single business group. Therefore, most of the transactions are affiliated transactions that must meet the Arm’s Length Principles. This study reviews the implementation of the Arm’s Length Principles in cash poolings. This research utilized a qualitative approach by reviewing elements of cash pooling transactions with Indonesia’s regulations and best practices in transfer pricing. The study concluded that implementing transfer pricing regulations in cash pooling arrangements would depend on the role of the leader. Based on the role of the leader, affiliated transactions in cash pooling are payment of loan interest and payment of interest on deposits in the scheme of the leader as an in-house bank and payment of fees in the scheme of the leader as a service provider. The transactions then need to be examined for compliance with the Arm’s Length Principles, including evaluating price indicators and selecting the tested party of each transaction.